Helmet fit assessment and concussion risk in youth ice hockey players: a nested case-control study - Gamble, A. S.; Bigg, J. L.; Sick, S.; Krolikowski, M.; Patton, D. A.; Hagel, B. E.; Emery, C. A. (Journal of Athletic Training, 2021)
Context: Injury surveillance has shown that concussions are the most common injury in youth ice hockey. Research examining the criteria for ensuring the correct fit of protective equipment and its potential relationship with concussion risk is very limited. Objective: To evaluate the association between helmet fit and the odds of experiencing a concussion among youth ice hockey players. Design: Nested case-control within a cohort study. Setting: Calgary, Alberta, Canada. Patients or Other Participants: Data were collected for 72 concussed, 41 nonconcussion-injured, and 62 uninjured ice hockey players aged 11 to 18 years. Main Outcome Measure(s): Helmet-fit assessments were conducted across players and encompassed helmet specifications, condition, certification, and criteria measuring helmet fit. Using a validated injury-surveillance system, we identified participants as players with suspected concussions or physician-diagnosed concussions or both. One control group comprised players who sustained nonconcussion injuries, and a second control group comprised uninjured players. Helmet-fit criteria (maximum score = 16) were assessed for the concussed players and compared with each of the 2 control groups. The primary outcome was dichotomous (>1 helmet-fit criteria missing versus 0 or 1 criterion missing). Logistic and conditional logistic regression were used to investigate the effect of helmet fit on the odds of concussion. Results: The primary analysis (54 pairs matched for age, sex, and level of play) suggested that inadequate helmet fit (>1 criterion missing) resulted in greater odds of sustaining a concussion when comparing concussed and uninjured players (odds ratio [OR] = 2.67 [95% CI = 1.04, 6.81], P = .040). However, a secondary unmatched analysis involving all participants indicated no significant association between helmet fit and the odds of sustaining a concussion when we compared concussed players with nonconcussion-injured players (OR = 0.98 [0.43, 2.24], P = .961) or uninjured players (OR = 1.66 [0.90, 3.05], P = .103). Conclusions: Inadequate helmet fit may affect the odds of sustaining a concussion in youth ice hockey players. Future investigators should continue to evaluate this relationship in larger samples to inform helmet-fit recommendations.